Այսրկովկասի հայկական գրատպութիւնը եւ Ներսէս արքեպիսկոպոս Շահազիզեանը - Պետոյեան, Ստեօպա; Սուքիասեան, Համօ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В XIX в. архиепископ Нерсес Аштаракеци имел значимый вклад в восточноармянскую действительность не только как национальный-духовный деятель, но и как поборник развития образования и культуры. Он считал особенно важным распространение и укрепление образования, книгоиздательской деятельности в армянской среде. Свидетельство тому основанное благодаря его усилиям издательство в Тифлисе и его плодотворная деятельность. По должности будучи духовным цензором армяноязычных книг Закавказья, он не только не препятствовал, но и способствовал издательству армяноязычных книг. Архиепископ Нерсес Аштаракеци не препятствовал и инициативе протестантских проповедников по распространению восточноармянского разговорного языка посредством печатной книги в Шуши. Деятельность Нерсеса Аштаракеци как духовного критика оказалось вне поля зрения исследователей, и данная статья призвана заполнить данное упущение, представляя архепископа как высокопоставленного армянского духовного деятеля, имеющего власть для осуществления духовной цензуры. Archbishop Nerses of Ashtarak made a significant contribution to the Eastern Armenian reality of the 19th century, not only as a national-spiritual figure, but also as an apologist for the development of education and culture. He particularly emphasized the expansion and strengthening of educational and publishing activities in the Armenian environment. The proof of this is the publishing house established in Tbilisi (Georgia) thanks to his efforts, and its fruitful activity. As a spiritual censor of the Armenian-language books of Transcaucasia, he not only did not interfere in, but also contributed to the publishing of the Armenian-language books. He did not prevent the initiative of Protestant preachers to spread the Eastern Armenian spoken language through a printed book in Shushi. The engagement of Archbishop Nerses of Ashtarak as a spiritual censor has not been a focus of study up to now, and the current article comes to fill the gap by investigating that aspect of his activities.
Keywords: Christianity; Literature